Application of Inner Mongolia electric power data warehouse - Yu ZHANG; Hongfang PAN (Dianxin kexue)
With the development of electric power information，the accumulation of power data is more and more fast，and the issue of how to make big data to support the scientific development of the company is increasingly mentioned. In the year of 2011，Inner Mongolia Power Company started to build integrated platform data center. The company has completed the company’s business data integration work，and provided a basis for the use of data. Based on the construction of integrated production and management decision-making analysis system，the Inner Mongolia Power Company in the data warehouse application exploration and attempt was introduced from the application needs，application technology，data analysis and mining. Summary of the results and experience of construction shows that the key of application analysis is demand management and the technology is datamining.